2021
DOI: 10.3389/fimmu.2021.679425
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Human Glioma Microenvironment

Abstract: Gliomas are the most common primary brain tumors in adults. Despite the fact that they are relatively rare, they cause significant morbidity and mortality. High-grade gliomas or glioblastomas are rapidly progressing tumors with a very poor prognosis. The presence of an intrinsic immune system in the central nervous system is now more accepted. During the last decade, there has been no major progress in glioma therapy. The lack of effective treatment for gliomas can be explained by the strategies that cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 89 publications
(105 reference statements)
1
97
0
Order By: Relevance
“…Moreover, the co-expression of PD-1 with other inhibitory receptors, such as PDL-1, TIM-3, LAG3, and CTLA-4, induces effector T cell exhaustion (73,74). It has also been reported that the PD-1/ PDL-1 pathway is significantly correlated with the most aggressive histological subtype of glioma (75,76). This could reflect the importance of the complex mechanisms established by the tumor microenvironment to suppress the antitumor immune response.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the co-expression of PD-1 with other inhibitory receptors, such as PDL-1, TIM-3, LAG3, and CTLA-4, induces effector T cell exhaustion (73,74). It has also been reported that the PD-1/ PDL-1 pathway is significantly correlated with the most aggressive histological subtype of glioma (75,76). This could reflect the importance of the complex mechanisms established by the tumor microenvironment to suppress the antitumor immune response.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, spearman correlation analysis was used to access the relationship between risk scores and the expression levels of common immune checkpoints, including programmed cell death 1 (PD1), programmed cell death-ligand 1 (PD-L1), cytotoxic T-lymphocyte associated protein 4(CTLA-4), Lymphocyte Activating 3 (LAG-3), T-cell immunoglobulin and mucin domain-containing protein 3 (TIM-3), B7-H3(CD276), T-cell immunoglobulin and ITIM domain (TIGIT) ( Ghouzlani et al, 2021 ; Yang et al, 2022 ) and two newly biomarkers APOBEC3B and TNFSF13 ( Zhang et al, 2021a ; Zhang et al, 2021c ). Then, we investigated the role of PRGs signature in predicting glioma immunotherapeutic response by the tumor immune dysfunction and exclusion (TIDE) algorithm ( http://tide.dfci.harvard.edu ).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decades, numerous therapies have been developed to treat cancers; however, few of them could effectively use in glioma. Despite the blood-brain barrier, unique structure in the CNS ( Oberoi et al, 2015 ), glioma cells adapted various strategies to escape the immune system also play an essential role ( Ghouzlani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, a collection of data has clarified the crucial role of the immune checkpoints in regulating the immune response in different cancer types. However, research on immunotherapy of glioma has extended in an exponential manner 4 7 . The majority of gliomas is obstinate to usual immunotherapies.…”
Section: Introductionmentioning
confidence: 99%